Understanding sociodemographic factors influencing households' financial literacy in Tanzania - Josephat Lotto (Cogent Economics & Finance, 2020)
This paper primarily aimed at examining the influence households' demographic characteristics on the level of their financial literacy in Tanzania. The paper employs secondary data from the FinScope survey conducted by Financial Sector Deepening Trust (FSDT). To do so, the study employed both bivariate and multivariate analytical techniques. The study, reveals that the adult population exhibits large financial literacy gap- and, therefore, adults should not be considered as a homogenous group- rather gender, age, education and income levels of the households, which are showcased in this study, to also be taken into consideration while designing financial literacy improvement public initiatives. In particular, the study concludes that men are more inclined to have higher levels of financial literacy than women something which limits their financial decisions making ability. It is also concluded that younger households and those with higher income levels are equipped with higher financial literacy levels. Likewise, more educated and employed households tend to have higher levels of financial literacy. It, therefore, follows that programs to foster financial knowledge among households should be targeted at marginalized groups like women, the elderly and those with low incomes and educational attainment. As the main contribution of the research, it is highlighted that this is a pioneer study in the Tanzanian context, by proposing a model that identifies which socioeconomic and demographic factors influence the propensity for a low or high financial literacy level.
Keywords: 330; age; education; financial literacy; gender